Coupled effects of morphology/length scale of the microstructure and microsegregation on the corrosion behaviour of a single-phase Zn-1wt%Cu alloy - Miranda, Romulo S.; Vida, Talita; Ligeiro, Henrique S.; Cheung, Noé; Simões, Fábio R.; Garcia, Amauri; Brito, Crystopher (Next materials, 2025)
Zn-Cu alloys are promising for biomaterials due to their unique properties. Unlike most metallic alloys, Zn-Cu exhibits a partition coefficient greater than 1, leading to solvent segregation. This study aims to explore how microsegregation and cellular microstructure affect the corrosion behaviour of a Zn-1wt%Cu alloy. Three specimens, with cellular spacings of approximately 8, 16, and 32 µm, were extracted from a directionally solidified casting. Electrochemical Impedance Spectroscopy and Potentiodynamic Polarization techniques were used to assess the corrosion performance in NaCl solutions. The results showed that coarser cellular structures demonstrated higher corrosion resistance, evidenced by greater charge transfer resistances and lower current densities. Corrosion initiated at the Cu-poor cellular boundaries, acting as anodic regions, and became more severe in finer microstructures. In contrast, larger cells with fewer boundaries exhibited less generalised corrosion, confirming that microstructural coarsening improves corrosion resistance. [Display omitted] •Directional solidification defines cell spacing in Zn-1wt%Cu alloy.•Cu microsegregation drives corrosion at cell boundaries.•Coarser microstructures show improved corrosion resistance.•EIS and polarization confirm lower icorr in larger λC samples.•Results support Zn-Cu alloy design for biodegradable implants.